Risk Analysis of Aircraft Maintenance, Repair and Overhaul (MRO) Project Delays Using a Fuzzy Logic Approach - Auliya Rasyid, Mochamad; Dinariyana, A. A. B. (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The aircraft MRO business is high-risk, particularly in terms of project delay for any reason such as workload limitation and acquisition of materials. This challenge is reflected in PT Garuda Maintenance Facility AeroAsia Tbk 2023 annual report performance where Service Level Agreement (SLA) realization was only 96.05% from the target of 100% and Customer Satisfaction Index (CSI) was 3.97, which is slightly off the target of 4.00. Subjective in nature, traditional risk analyses are. This study aims to objectively identify and quantify risk factors causing delay of MRO projects and formulate risk treatment plans. The methodology integrates expert interviews with fuzzy set theory for the quantification of qualitative data and is organized with the use of the ISO 31000 risk management standard. From analysis of 20 risk variables, it was determined that material-related problems are the most prevalent cause of delay. In particular, material delivery delay (R09) was the most critical with a risk score of 89.31%, followed by equipment damage and limitations (R02) and warehouse material shortages (R11). These results reflect the high-risk operating conditions for MRO projects where 75% of the risks were "High" in classification. The study concludes fuzzy logic application was successful in quantifying subjective expert views, being a more objective and nuanced basis on which to rank the risks than conventional methods. The ultimate risk ranking serves as an important tool for management with which to develop targeted risk treatment programs, highlighting improving supply chain control, improving equipment reliability, and streamlining workload manpower planning in the aim of achieving SLA and overall operational efficiency improvements.